Reputation
17,337
Top tag
Next privilege 20,000 Rep.
Access 'trusted user' tools
Badges
2 12 58
Newest
 Good Answer
Impact
~161k people reached

11h
asked A functional equation relating two harmonic sums.
13h
awarded  Good Answer
18h
comment recurrence relation for Strassen's matrix multiplication
This has appeared here several times, consult e.g. the following MSE link.
2d
answered Show that $ \sum_{k=0}^{r} \binom{r-k}{m} \binom{s+k}{n} = \binom{r+s+1}{m+n+1} $?
Aug
27
answered Simplifying $\sum_{i=0}^n i^k\binom{n}{2i+1}$
Aug
27
comment Prof Gould combinatorial identity 3.27 and its “cousin” formula
It seems correct to me. The positive sign is because we filter the even terms rather than the odd ones as in the other answer. (I suggest you compare the two answers.) Of course the power of the square root term refers to it being raised to the power $2x+1$ which looks correct as well.
Aug
26
answered How to closed the sum $\displaystyle \sum_{k=0}^n \dfrac{(-1)^k(2k+1)!!}{(n-k)!k!(k+1)!}$
Aug
26
revised Average length of a cycle in a n-permutation
maple
Aug
26
revised Average length of a cycle in a n-permutation
trivial
Aug
26
answered Average length of a cycle in a n-permutation
Aug
26
revised Calculate a multiple sum of inverse integers.
format
Aug
25
answered Calculate a multiple sum of inverse integers.
Aug
25
revised Prove that $\sum_{k=0}^{m}\binom{m}{k}\binom{n+k}{m}=\sum_{k=0}^{m}\binom{n}{k}\binom{m}{k}2^k$
missing differential
Aug
25
revised How prove this$\sum_{i=0}^{m-1}\binom{n-1+i}{i}x^ny^i+\sum_{j=0}^{n-1}\binom{m-1+j}{j}x^my^j=1$
language usage
Aug
25
revised How prove this$\sum_{i=0}^{m-1}\binom{n-1+i}{i}x^ny^i+\sum_{j=0}^{n-1}\binom{m-1+j}{j}x^my^j=1$
linkage
Aug
25
comment How prove this$\sum_{i=0}^{m-1}\binom{n-1+i}{i}x^ny^i+\sum_{j=0}^{n-1}\binom{m-1+j}{j}x^my^j=1$
An algebraic proof using complex variables is now included on this page.
Aug
25
answered How prove this$\sum_{i=0}^{m-1}\binom{n-1+i}{i}x^ny^i+\sum_{j=0}^{n-1}\binom{m-1+j}{j}x^my^j=1$
Aug
24
awarded  Electorate
Aug
24
revised Let $g_{n}$ be the no. of derangements with $n$ elements and $f_{n}$ the no. of permutations with one fixed point. Show that $|g_{n}-f_{n}|=1$
stray character
Aug
24
answered Let $g_{n}$ be the no. of derangements with $n$ elements and $f_{n}$ the no. of permutations with one fixed point. Show that $|g_{n}-f_{n}|=1$